2018
DOI: 10.22435/mpk.v28i3.254
|View full text |Cite
|
Sign up to set email alerts
|

Hubungan Kejadian Karies Gigi dengan Konsumsi Air Minum pada Masyarakat di Indonesia

Abstract: The prevalence of dental caries in Indonesia is quite high, the results of the 2013 Basic Health Research (Riskesdas) population in Indonesian with 25,9% problems with their teeth and mouth. The average dental caries measured by the DMF-T index was 4.6, which means that the average Indonesian population has experienced tooth decay as much as 5 teeth per person. Dental caries can occur due to low dental and oral hygiene, and less exposure to fluorida. The incidence of dental caries is also related to the fluori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
6

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 8 publications
0
2
0
6
Order By: Relevance
“…Air dapat dikategorikan bersih apabila syarat fisik, kimia, bakteriologis dan radioaktif dalam batas yang ditetapkan oleh pemerintah meskipun air relatif melimpah, tetapi masih dijumpai masyarakat yang kesulitan mendapat air bersih. 4 Hal tersebut disebabkan karena banyak air yang telah tercemari oleh berbagai limbah aktivitas manusia. Air yang mengandung logam dan bersifat asam (pH<7) ialah suatu faktor yang memengaruhi demineralisasi dan apabila dibiarkan akan membentuk rongga sehingga menyebabkan timbulnya karies.…”
Section: Pendahuluanunclassified
“…Air dapat dikategorikan bersih apabila syarat fisik, kimia, bakteriologis dan radioaktif dalam batas yang ditetapkan oleh pemerintah meskipun air relatif melimpah, tetapi masih dijumpai masyarakat yang kesulitan mendapat air bersih. 4 Hal tersebut disebabkan karena banyak air yang telah tercemari oleh berbagai limbah aktivitas manusia. Air yang mengandung logam dan bersifat asam (pH<7) ialah suatu faktor yang memengaruhi demineralisasi dan apabila dibiarkan akan membentuk rongga sehingga menyebabkan timbulnya karies.…”
Section: Pendahuluanunclassified
“…Hal ini menunjukan ada pola konsumsi makanan tinggi kolestrol, lemak, dan sodium yang merupakan faktor risiko hipertensi ditinjau dari konsumsi makanan. Hal ini dikarenakan konsumsi tinggi kolestrol dan lemak akan memicu terjadinya aterosklerosis, serta asupan garam akan mempengaruhi tekanan darah (Indrawati et al, 2009).…”
Section: Pendahuluanunclassified
“…Caries is also related to education and work as well as location of residence. 16,21,22 The behavior of coastal communities that can affect the incidence of caries is the behavior of Caries can also be experienced by children as shown by the research of Das, et al (2013) in the coastal areas of West Bengal India. The results showed that caries in permanent teeth in the age category 6-8 years was 15.11% with 8.4% males (mean DMF-T 1.53) and 6.71% females (mean DMF-T 1.67).…”
Section: Behaviormentioning
confidence: 99%